Management of Performance Management Using Balanced Scorecard Method - Lestari, Rina Anggi; Slamet, Achmad (Management Analysis Journal, 2018)
The aims of this research is to describe and analyze the level of performance management of RSUD Dr. Soeselo Kabupaten Tegal using the Balanced Scorecard method. Sampling was carried out by incidental sampling the sample size was determined using the formula slovin and obtained 100 respondens. Data collection methods used are documentation and questionnaires. The analytical method used is descriptive quantitative analysis. The results obtained, in 2015-2017 performance of the financial perspective was considered good. Cutomer perspective performance is considered good. The performance of learning and growth is considered good. The conclusions of this study is the overall performance of RSUD Dr. Soeselo Kabupaten Tegal is categorized quite well. Suggestion in observational it is advisable RSUD Dr. Soeselo Kabupaten Tegal needs to increase motivation and training for employees, so that it can contribute to improving the performance of hospital services.